Acute phase response to exertional heat stroke in mice. Issue 1 (12th May 2020) - Iwaniec, John; Robinson, Gerard P.; Garcia, Christian K.; Murray, Kevin O.; de Carvalho, Lucas; Clanton, Thomas L.; Laitano, Orlando
Abstract : New Findings: What is the central question of this study? Exertional heat stroke is accompanied by a marked inflammatory response. In this study, we explored the time course of acute phase proteins during recovery from severe heat stress in mice and the potential role of skeletal muscles as their source. What is the main finding and its importance? Exertional heat stroke transiently increased expression of acute phase proteins in mouse liver and plasma and depleted liver and plasma fibrinogen, a typical response to severe trauma. In contrast, skeletal muscle fibrinogen production was stimulated by heat stroke, which can provide an additional reservoir for fibrinogen supply to maintain the clotting potential throughout the body and locally within the muscle. Abstract: Exertional heat stroke (EHS), the most severe manifestation of heat illness, is accompanied by a marked inflammatory response. The release of acute phase proteins (APPs) is an important component of inflammation, which can assist in tissue survival/repair. The time course of APPs in recovery from EHS is unknown. Furthermore, skeletal muscles produce APPs during infection, but it is unknown whether they can produce APPs after EHS. Our objective was to determine the time course of representative APPs in liver, plasma and skeletal muscle during recovery from EHS. Male C57BL6/J mice ran in a forced running wheel at 37.5°C, 40% relative humidity until symptom limitation. Exercise control (EXC) mice ran for the same duration and intensity at 22.5°C. Samples were collected ( n = 6–12 per group) over 14 days of recovery. Protein abundance was quantified using immunoblots. Total and phosphorylated STAT3 (pSTAT3) at Tyr705, responsible for APP activation, increased in liver at 0.5 h after EHS compared with EXC, ( P < 0.05 and P < 0.001, respectively). In contrast, in tibialis anterior (TA) muscle, total STAT3 increased at 3 h ( P < 0.05) but pSTAT3 (Tyr705) did not. Liver serum amyloid A1 (SAA1) increased at 3 and 24 h after EHS ( P < 0.05), whereas plasma SAA1 increased only at 3 h ( P < 0.05). SAA1 was not detected in TA muscle. In liver and plasma, fibrinogen decreased at 3 h ( P < 0.01) and increased in TA muscle ( P < 0.05). Lipocalin‐2 was undetectable in liver or TA muscle. Recovery from EHS is characterized by a transient acute phase response in both liver and skeletal muscle. However, APP expression profiles and subtypes differ between skeletal muscle and liver. Abstract :